Do You Love Nature if You Fear Her Body? Style, Narrative Perspective, and the Southern Wilderness in Faulkner’s «The Bear» - Brøgger, Fredrik Chr. (Nordlit, 1998)
In the title above, the question and its reference to ‘her’ are willfully ambiguous (…).